Association between Social Jetlag and Objective Physical Activity among Female University Students of Japan: A Cross-Sectional Study - Shibata, Masashi; Fujibayashi, Mami; Shibata, Shiori; Kuzuhara, Kenji; Tanida, Keiko (Sleep Science, 2024)
Objective Discrepancies between sleep timing on work/school and free days, also known as social jetlag (SJL), can cause health problems. These issues occur most often in individuals from adolescence to the early 20s, which is equivalent to the age of university students. This study was designed to explore the recommended level of physical activity required to minimize SJL and to examine the relationship between SJL and objective physical activity among female university students.Methods We assessed the SJL of 68 female students using the Japanese version of the Munich Chronotype Questionnaire. The objective physical activity and sleep variables of subjects were also evaluated at 3 to 4 weeks using a small triaxial accelerometer.Results A significant negative correlation was found between SJL and physical activity on both free (r = − 0.435, p < 0.001) and school days (r = − 0.341, p < 0.01). According to the linear regression analysis, physical activity of 11,174 steps on school days and 10,713 steps on free days had the lowest SJL value. Total sleep time on free days had a significant positive correlation with SJL (r = 0.399, p < 0.001) and a negative correlation with physical activity (r = − 0.520, p < 0.001).Discussion Our results suggest that substantial SJL may cause chronic fatigue and lead to a low level of physical activity in female university students. These results also imply that the recommended level of physical activity necessary to minimize SJL among these students is around 11,000 steps on both school and free days.
Keywords: social jetlag; physical activity; circadian rhythm; university students